2020
DOI: 10.1016/j.molmet.2020.101089
|View full text |Cite
|
Sign up to set email alerts
|

P2Y2R contributes to the development of diabetic nephropathy by inhibiting autophagy response

Abstract: Objective Diabetic nephropathy (DN) is one of the most common complications of diabetes and a critical risk factor for developing end-stage renal disease. Activation of purinergic receptors, including P2Y2R has been associated with the pathogenesis of renal diseases, such as polycystic kidney and glomerulonephritis. However, the role of P2Y2R and its precise mechanisms in DN remain unknown. We hypothesised that P2Y2R deficiency may play a protective role in DN by modulating the autophagy signallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 63 publications
2
27
0
Order By: Relevance
“…35 Other research has shown that the phosphorylation of ULK-1 was also reduced when autophagy was enhanced in diabetic nephropathy. 36 In the present study, we found that the administration of 5-PAHSA reduced the phosphorylation of m-TOR in both PC12 cells under diabetic condition and DB/DB mice. progression of AD and extend life span in transgenic mouse models of AD.…”
Section: Discussionsupporting
confidence: 59%
“…35 Other research has shown that the phosphorylation of ULK-1 was also reduced when autophagy was enhanced in diabetic nephropathy. 36 In the present study, we found that the administration of 5-PAHSA reduced the phosphorylation of m-TOR in both PC12 cells under diabetic condition and DB/DB mice. progression of AD and extend life span in transgenic mouse models of AD.…”
Section: Discussionsupporting
confidence: 59%
“…To assess the effect of geniposide on tubular damage, the expression of these biomarkers was evaluated by real-time PCR analysis. Consistent with our previous findings [28], the mRNA levels of KIM-1 and NGAL were significantly upregulated in DN mice compared to control, but reduced by geniposide treatment (Figure 2A). The protective effect of geniposide was further confirmed by PAS staining; DN mice showed a significant increase of tubulo-interstitial damage including tubular dilatation, loss of brush borders, necrosis and extracellular accumulation, which was reduced by geniposide treatment ( Figure 2B, damaged tubules are indicated by black arrows).…”
Section: Geniposide Reduced Renal Tubular Injury and Interstitial Fibsupporting
confidence: 92%
“…Renal histological abnormalities were assessed semi-quantitatively as previously described [28]. Briefly, after PAS staining, the severity of the glomerular injury was evaluated in randomly selected fields at 400× magnification and graded as follows: grade 0 = normal, grade 1 = <25%, grade 2 = 25-50%, grade 3 = 50-75% and grade 4 = 75-100% of segmental lesions.…”
Section: Kidney Histological Examinationmentioning
confidence: 99%
“…Huang et al identified KCa3.1 (calcium-activated K+ channel) involved in renal tubular autophagy dysfunction through PI3K/Akt/mTOR signaling pathway in DKD (94). Theodomir et al confirmed that P2Y2R deficiency increased the expression of sirtuin-1 and FOXO3a, which enhanced autophagy and improved renal insufficiency in DKD (95). In addition, Yang et al found that Smad3, the downstream transcription factor activated by TGFβ (transforming growth factor β), suppressed lysosome biogenesis in a TFEB-dependent manner (96).…”
Section: Autophagymentioning
confidence: 99%